Connecting Vegetable Gardens in Schools and in Homes: A Sustainable Model for Nutrition Security in Nepal - Bhattarai, Dhruba Raj (Journal of the Institute of Agriculture and Animal Science, 2024)
School vegetable gardening is an effective concept to enhance people’s inclination towards eating more vegetables. It increases children’s knowledge and awareness regarding the importance of vegetables for nutrition in health. School vegetable gardening also contributes to children’s physical wellbeing and social skills. Linked with home gardens it can contribute to healthier diets. Based on experiences and evidence of school and home gardening projects this concept paper has been prepared. The purpose is to make an effective contribution to program planning to overcome the extensive problem of micronutrient deficiencies and for boosting immune system of individuals.